Avatar, the last airbender. Book 2. Earth [videorecording (DVD)] - DiMartino, Michael Dante; Konietzko, Bryan (Paramount, 2015)
"Avatar Aang continues his quest to master the four elements as he and his friends journey across the Earth Kingdom in search of an Earthbending mentor. But they soon run into Princess Azula, the treacherous and power-mad sister of Prince Zuko ... and she will stop at nothing to defeat the Avatar."--Container